2017
DOI: 10.1002/lno.10495
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, biological uptake, and respiration of dissolved acrylate and dimethylsulfoxide in the northern Gulf of Mexico

Abstract: The abundant marine organosulfur compound, dimethylsulfoniopropionate (DMSP) can be degraded to acrylate and dimethylsulfide (DMS), with some DMS further oxidized to dimethylsulfoxide (DMSO). Despite intensive study of DMSP and DMS in a variety of marine settings, the processes affecting acrylate and DMSO concentrations in marine waters are poorly known, particularly their loss from the dissolved phase through biological uptake. We measured the concentrations of dissolved acrylate (acrylate d ) and DMSO (DMSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 84 publications
3
34
2
Order By: Relevance
“…Likewise, the total uptake of acetate accounted for 0.1–0.2% of the BCD (excluding site GB848; Table ). These contributions of acetate to the BCD were slightly higher than observed for acrylate (0.01–0.13%) and dimethylsulfoxide (0.04–0.14%) in the Gulf of Mexico (Tyssebotn et al, ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Likewise, the total uptake of acetate accounted for 0.1–0.2% of the BCD (excluding site GB848; Table ). These contributions of acetate to the BCD were slightly higher than observed for acrylate (0.01–0.13%) and dimethylsulfoxide (0.04–0.14%) in the Gulf of Mexico (Tyssebotn et al, ).…”
Section: Discussionmentioning
confidence: 70%
“…Incubations were terminated by adding 100 μL of ice‐cold 100% TCA. BCP were calculated based on the theoretical leucine to carbon conversion factor (LCF) of 1.5‐kg C/mol leucine (Kirchman, ; Simon & Azam, ; equation ); this LCF value was used recently in the northern Gulf of Mexico (Tyssebotn et al, ). BCP=()BP×LCF/MM where BP is the meausred leucine incorporation rate (nmol·L −1 ·day −1 ) and MM is the molar mass of carbon (12 g/mol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the DMSO yield from DMS photo-oxidation apparently varies between shelf seas (25%), polar waters (39%) and the open ocean (14%) (Kieber et al, 1996;Hatton, 2002;Toole et al, 2004). Even so, DMSO concentrations frequently exceed those of DMS (Lee et al, 1999), possibly due to a lack of photochemical removal (Toole et al, 2004), slow microbial consumption (Tyssebotn et al, 2017), significant biological production (Del Valle et al, 2007a) or an aggregate of all three.…”
Section: Introductionmentioning
confidence: 99%
“…Kinsey et al (2016) explored the effects of iron limitation and UV radiation on Phaeocystis antarctica growth and AA concentrations. The concentrations, biological uptake, and respiration of dissolved AA (AAd) were investigated in the northern Gulf of Mexico (Tyssebotn et al, 2017). Tan et al (2017) and Wu et al (2017) reported the spatial distributions of AA in the Changjiang Estuary and the East China Sea.…”
mentioning
confidence: 99%